FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MASYARAKAT MENGGUNAKAN LAYANAN PERBANKAN SYARIAH - Amalia, Rizqi; Anwar, Mukhlis Kaspul; Malihah, Lola; Aisyah, Lisda (Indonesian Scientific Journal of Islamic Finance, 2023)
The function and role of Islamic financial institutions include meeting the needs of the community for funds as a means to carry out economic activities in accordance with sharia principles. The purpose of this study is to find out what factors affect people's decisions using Islamic banking services. Researchers tested several variables that allegedly influence people's decisions using Islamic Banking services, namely knowledge (X1), fund products and services (X2) and quality of service (X3). At the coefficient of determination (R Square) of 0.615 or equal to 61.5%. This means that knowledge variables, funded products and services and service quality simultaneously (together) can explain the response variable by 61.5%. The rest (100% - 61.5% = 38.5%) was explained by other variables outside of the study. Keywords: Quality of Services, Funded Products and Services.